2014
DOI: 10.5430/mos.v2n1p25
|View full text |Cite
|
Sign up to set email alerts
|

Triple Bottom Line: A Look at Talent Acquisition and Employee Engagement Using Grounded Theory

Abstract: This paper is based on a study that explored triple bottom line (TBL) as an emerging phenomenon using grounded theory. Presented here are the results from the section concerning talent acquisition and employee engagement of the original study. The presented results suggest that TBL Image (a term developed in the study) is positively associated with talent acquisition and employee engagement. This is illustrated by the introduction of the TBL Image Diagram, which provides an insight into how the image of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…From a triple bottom line approach, a reciprocal relationship exists between the organisation and talent preferences. A study by Alhaddi (2015) showed that new talents, such as Generation Y, are more likely to be attracted, retained, and engaged in organisations that follow a triple-bottom-line approach.…”
Section: Rethinking the Current Paradigms For Talent Management: The ...mentioning
confidence: 99%
“…From a triple bottom line approach, a reciprocal relationship exists between the organisation and talent preferences. A study by Alhaddi (2015) showed that new talents, such as Generation Y, are more likely to be attracted, retained, and engaged in organisations that follow a triple-bottom-line approach.…”
Section: Rethinking the Current Paradigms For Talent Management: The ...mentioning
confidence: 99%